A robotic protocol for high‐throughput processing of samples for selected reaction monitoring assays. Issue 6 (23rd December 2016) - Zhu, Min; Zhang, Pingbo; Geng‐Spyropoulos, Minghui; Moaddel, Ruin; Semba, Richard D.; Ferrucci, Luigi
Abstract : Selected reaction monitoring mass spectrometry (SRM‐MS) is a sensitive and accurate method for the quantification of targeted proteins in biological specimens. However, the sample throughput and reliability of this technique is limited by the complexity of sample preparation, as well as instrumentation and data processing. Modern robotic equipment allows for rapid and accurate processing of large number of samples and makes SRM‐MS assay applicable in epidemiological studies. Herein, we describe an automated sample processing platform developed in the context of an SRM‐MS protocol for the assay of complement factor H protein and its variants in human plasma. We report detailed performance data on plasma digestion, sample cleanup and optimized robotic handling implemented on a Biomek ® NX p Workstation. Method validation was assessed with isotopically labeled peptide standards and had high reproducibility of intra‐day assay (CVs from 2.7 to 17.5% with median CV of 5.3%) and inter‐day assay (CVs from 4.8 to 17.6 with median CV of 7.2%) for all peptides.